GLP-1 RAs and SGLT2i: two antidiabetic agents associated with immune and inflammation modulatory properties through the common AMPK pathway - Mazzieri, Alessio; Basta, Giuseppe; Calafiore, Riccardo; Luca, Giovanni (Frontiers in Immunology, 2023)
Either immune or not immune cells respond to nutrients deprivation by the classic cathabolic pathway of AMPK (Adenosine monophosphate kinase). This kinase is a pivotal regulator of glucose and fatty acids metabolism, although current evidences highlight its role in immune regulation. Indeed AMPK, by activation of Foxo1 (Forkhead box O1) and Foxo3 (Forkhead box O3) can regulate FOXP3, the key gene for differentiation and homeostasis of Tregs (T regulators lymphocytes). The relevance of Tregs in the onset of T1D (Type 1 diabetes) is well-known, while their role in the pathogenesis of T2D (Type 2 diabetes) is not fully understood yet. However, several studies seem to indicate that Tregs may oppose progression of diabetic complications thanks to the fight against insulin resistance, atherosclerosis and damage of target organs (as kidney disease). Hence, AMPK and AMPK-activating agents may play a role in the regulation of the immune system. The connection between metformin and AMPK is historically known; on the contrary this link and the possible related immune effects are less studied about SGLT2i (Sodium-glucose co-transport 2 inhibitors) and GLP1-RAs (Glucagon-like peptide-1 receptor agonists). Actual evidences show that the negative caloric balance, induced by SGLT2i, can activate AMPK. Conversely and surprisingly, also an anabolizing agent like GLP-1RAs, can upregulate this kinase, through cAMP (Cyclic adenosine monophosphate) accumulation. Therefore, both these drugs can likely lead to activation of the AMPK-pathway and consequential proliferation of Tregs. These observations seem to confirm the not only metabolic but also immunoregulatory effects of these new antidiabetic agents.